2007
DOI: 10.1089/end.2007.9946
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Advancement with End-to-End Reconstruction after Partial Neurovascular Bundle Resection:A Feasibility Study

Abstract: We are encouraged by the initial results of NAT. The procedure may be an alternative for men who require extensive NVB dissection. However, further experience, longer follow-up, and independent trials are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In patients with palpable and more aggressive cancer needing wide local excision, the technique of nerve advancement and end‐to‐end anastomosis has recently been described. A small group of patients appeared to achieve earlier erectile potency after this surgical modification to RARP 26 …”
Section: Potency and Quality Of Lifementioning
confidence: 92%
See 1 more Smart Citation
“…In patients with palpable and more aggressive cancer needing wide local excision, the technique of nerve advancement and end‐to‐end anastomosis has recently been described. A small group of patients appeared to achieve earlier erectile potency after this surgical modification to RARP 26 …”
Section: Potency and Quality Of Lifementioning
confidence: 92%
“…A small group of patients appeared to achieve earlier erectile potency after this surgical modification to RARP. 26 It is important to avoid the use of thermal energy during nerve sparing. Ahlering and colleagues had reported the deleterious effects of cautery on potency and recently updated their results in patients where either monopolar or bipolar cautery had been used for nerve sparing.…”
Section: Potency and Quality Of Lifementioning
confidence: 99%
“…In addition, various grades of NS are possible [32]. It is possible to either resect a small segment of the neurovascular tissue and repair the gap by primary anastomosis [33], or shave off the medial aspect of neurovascular tissue (i.e. incremental NS) to meet the most important goal of surgery, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the ideal method for NVB reconstruction. While there are a few existing options to choose from, namely sural nerve grafting,[49] use of embryonic stem cells or growth factors to enhance neural regeneration,[50] entubulization model of cavernosal nerve[51] or nerve advancement with end-to-end reconstruction,[52] none of them are employed routinely.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that NAT is technically feasible, oncologically safe and is associated with promising sexual outcomes. [52]…”
Section: Introductionmentioning
confidence: 99%